How Physician Perspectives on E-Prescribing Evolve over Time - Abramson, Erika L.; Patel, Vaishali; Pfoh, Elizabeth R.; Kaushal, Rainu (Applied Clinical Informatics, 2016)
Background Physicians are expending tremendous resources transitioning to new electronic health records (EHRs), with electronic prescribing as a key functionality of most systems. Physician dissatisfaction post-transition can be quite marked, especially initially. However, little is known about how physicians’ experiences using new EHRs for e-prescribing evolve over time. We previously published a qualitative case study about the early physician experience transitioning from an older to a newer, more robust EHR, in the outpatient setting, focusing on their perceptions of the electronic prescribing functionality.Objective Our current objective was to examine how perceptions about using the new HER evolved over time, again with a focus on electronic prescribing.Methods We interviewed thirteen internists at an academic medical center-affiliated ambulatory care clinic who transitioned to the new EHR two years prior. We used a grounded theory approach to analyze semi-structured interviews and generate key themes.Results We identified five themes: efficiency and usability, effects on safety, ongoing training requirements, customization, and competing priorities for the EHR. We found that for even experienced e-prescribers, achieving prior levels of perceived prescribing efficiency took nearly two years. Despite the fact that speed in performing prescribing-related tasks was highly important, most were still not utilizing system short cuts or customization features designed to maximize efficiency. Alert fatigue remained common. However, direct transmission of prescriptions to pharmacies was highly valued and its benefits generally outweighed the other features considered poorly designed for physician workflow.Conclusions Ensuring that physicians are able to do key prescribing tasks efficiently is critical to the perceived value of e-prescribing applications. However, successful transitions may take longer than expected and e-prescribing system features that do not support workflow or require constant upgrades may further prolong the process. Additionally, as system features continually evolve, physicians may need ongoing training and support to maintain efficiency.Citation: Abramson EL, Patel V, Pfoh RE, Kaushal R. How physician perspectives on E-prescribing evolve over time: A case study following the transition between EHRs in an outpatient clinic.
Keywords: Physician perspective; EHR; transition; e-prescribing